The Economic Determinants of Executive Stock Options Grants in Portuguese Firms - Sandra Alves (Journal of Accounting, Business and Management (JABM), 2011)
This study investigates the economic justifications of stock options grants in Portuguese firms. We hypothesize that the agency theory (firm size, firm risk, diversification and investment opportunities), financial (liquidity constraints and leverage), ownership (equity held by managers and ownership concentration) and board structure may influence the grant of stock options in Portuguese firms. Using a sample of 160 observations (40 firm-year observations from 2003 to 2006), from Portuguese listed firms we find that the probability of granting stock options increases with the firms size, when firms face liquidity constraints and managerial ownership is high, and decreases with firms risk, when diversification is high and when firms have high levels of investment opportunities and of leverage.